The effect of the transmission line radiation on human physical condition using resonant field imaging (RFI™) / Afzan Zainal - Zainal, Afzan
This paper provides information on the effect of the transmission line (TL) radiation on human physical condition. To analyze this effect, the technology called Resonant Field Imaging (RFI) is used. Three to five weeks measurements are conducted to conclude the health conditions caused from TL using the RFI equipment called hand held digital frequency counter. It is used to measure frequencies around human body. The RFI software is then used to interpret these frequencies in terms of aura and bio-energy. From the RFI interpretation, the new program has been developing using Visual Basic 6.0 (VB 6.0) to analyze all data. Results on this paper will generates the useful information on which part of human physical condition are probably effected by the TL radiation.